The Social Challenges of Modern State-Building in Afghanistan - Hussaini, Sayed Mahdi (Technium Social Sciences Journal, 2021)
Empirical-historical evidences indicated that the process of state-building in the third world and developing countries has not been performed successfully and has faced important crises such as identity crisis, legitimacy, nation-building, and ethnic-religious violence. The present study aimed to identify the important social barriers or challenges or state-building in the current Afghanistan. Based on the hypothesis, ethnic gaps, identity crisis, violence caused by such active and rooted gaps, destructive role-playing of Talibanism and biased sectarianism of this current, cultural poverty, and severe traditional natuSre of society were considered as the significant challenges or barriers of inclusive state-building in Afghanistan. In this study, the above-mentioned problem was studied in the framework of failed state theory through a sociological-scientific explanation. Historical evidence from the past century ago indicated that ethnic-religious gaps and the resulted identity crisis have worked as important challenges and barriers of inclusive state-building in Afghanistan and the crisis in the last presidential elections can be analyzed in this regard.